Tryptophan depletion in normal volunteers produces selective impairments in learning and memory. - Park, S; Coull, J; McShane, R; Young, A; Sahakian, B; Robbins, T; Cowen, P (1994)
The amino-acid L-tryptophan is essential in the synthesis of brain serotonin, and its depletion can lead to a widespread reduction in central serotonergic activity. A placebo-controlled cross-over within-subjects design (n = 12) examined the effects of tryptophan depletion on human cognitive performance. A low-tryptophan (low-TRP) drink successfully reduced the levels of plasma and total free tryptophan. Computerized tests of memory, learning and executive function revealed selective and non-sedative impairments on cognitive performance following the active drink. Specifically, low-TRP impaired learning as seen in tests of visual discrimination and paired associates. Furthermore, low-TRP lengthened thinking times during the Tower of London planning task, but only in subjects already familiar with the task, suggesting a retrieval deficit. No evidence was found for an effect of the low-TRP drink on measures sensitive to frontal lobe dysfunction, supporting instead a specific role for the serotonergic system in the processes of memory and learning not directly implicated in frontal lobe function.